Kontekstualisasi nilai-nilai pendidikan dalam kitab al-barzanji karya Syaikh Ja’far al-Barzanji dalam perspektif ulama kota Palopo - Muhammad Zainal Abidin; Syahruddin; Bustanul Iman RN (At Turots: Jurnal Pendidikan Islam, 2023)
This study aims: 1) To describe the educational values ​​in the book of al-Barzanji. 2) To find out the contextualization of educational values ​​in the book of al-Barzanji. 3) To find out what are the supporting and inhibiting factors for the contextualization of educational values ​​contained in the book of al-Barzanji. This type of research is descriptive qualitative research. This research is intended to raise the facts, circumstances, variables, and phenomena that occur. The research approach is sociological psychological pedagogy. The data sources used are primary data and secondary data. Data collection techniques and instruments are observation, interviews and documentation. The results of this study indicate that, 1) Faith and piety, gratitude, humility, honesty, kindness, fairness, and patience are the educational values ​​outlined in the book al-Barzanji. Through the naming of Islamic values, moral and physical development, and the production of changes in a positive direction, moral education is an activity that is carried out consciously and intentionally to provide physical and spiritual development. 2) Contextualization of the value of education in Kitab al-Barzanji, namely teaching love for the Messenger of Allah through prayer for him, being a da'wah method lading, being a conditioner in family life and the general public, having a good personality, religious character values ​​in educating children, teaching values exemplary and strengthen the value of humility or humility, have a friendly attitude, honest, fair and grateful. 3) Factors supporting and inhibiting the contextualization of educational values ​​contained in the book of al-Barzanji. The supporting factors are happy people, support from religious instructors and the existence of the al-Barzanji book. While the inhibiting factor is that people do not like reading al-Barzanji, and reading al-Barzanji is used as worship